Comparison of the second-line treatment efficacy in advanced gastric cancer patients previously treated with taxane-based triplet chemotherapy: a Turkish Oncology Group Study - Bir Yucel, Kadriye; Ugrakli, Muzaffer; Sekmek, Serhat; Yildirim, Nilgun; Gurler, Fatih; Yazici, Ozan; Ozdemir, Nuriye (Taylor & Francis Ltd, 2024)
ObjectiveThis study aimed to assess the efficacy and safety of FOLFIRI and paclitaxel in patients with advanced gastric cancer (AGC) who were previously treated with first-line modified docetaxel, cisplatin, 5-fluorouracil (mDCF), or 5-fluorouracil, oxaliplatin, docetaxel (FLOT).MethodsPatients who received a triplet regimen in the first line setting and were treated with FOLFIRI or paclitaxel in the second-line treatment were included.ResultsThe study included 198 patients, with 115 receiving FOLFIRI and 83 receiving paclitaxel. The median age was 58 (range = 24-69). The median progression-free survival (mPFS) was 5.2 [95% confidence interval (CI) = 4.4-5.5] months in the FOLFIRI arm, and 4.1 (95% CI = 3.3-4.6) months in the paclitaxel arm (p = .007). The median overall survival (mOS) was 9.4 (95% CI = 7.4-10.5) months in the FOLFIRI arm and 7.2 (95% CI = 5.6-8.3) months in the paclitaxel arm (p = .008). Grade 3-4 neuropathy was higher in patients receiving paclitaxel compared to those receiving FOLFIRI (p = .04). Grade 3-4 diarrhea was 8% in the FOLFIRI arm and 2.4% in the paclitaxel arm (p = .02).ConclusionBeyond progression with docetaxel-based triplet chemotherapy, FOLFIRI may be preferred as a second-line treatment over paclitaxel due to its longer mPFS and mOS.
Keywords: Gastric cancer; taxane; metastatic; survival; FOLFIRI